The epidemiology of progressive intellectual and neurological deterioration in childhood. Issue 5 (29th November 2009) - Verity, Christopher; Winstone, Anne Marie; Stellitano, Lesley; Will, Robert; Nicoll, Angus
Abstract : Objective: To study the epidemiology of diseases that cause progressive intellectual and neurological deterioration (PIND) in UK children. Design: Since May 1997, the authors have performed active surveillance to search for variant Creutzfeldt–Jakob Disease (vCJD) among the many diseases that cause neurological deterioration in children, using the monthly surveillance card sent to all UK consultant paediatricians by the British Paediatric Surveillance Unit. The authors obtain clinical details from reporting paediatricians by questionnaire or site visit, and an Expert Group then independently classifies the cases. Results: After 12 years, 2636 patients less than 16 years old with suspected PIND had been reported, of whom 1114 had a confirmed diagnosis to explain their deterioration: in these children, there were 147 different diseases. These were the six commonest diagnostic groups: leukoencephalopathies (183 cases), neuronal ceroid lipofuscinoses (141 cases), mitochondrial diseases (122 cases), mucopolysaccharidoses (102 cases), gangliosidoses (100 cases) and peroxisomal disorders (69 cases). Relatively large numbers of PIND children were reported from parts of the UK where there are high rates of consanguinity. Only six children with vCJD (four definite, two probable) had been identified. Conclusions: Although this study does not ascertain all UK cases, it provides a novel insight into the epidemiology of the neurodegenerative diseases that cause PIND in children. It is reassuring that in general these children are carefully investigated and that active surveillance has found only six children with vCJD. However, there is concern that more childhood vCJD cases may appear, possibly with a different genotype from those identified so far.